Is the National Health Insurance Scheme helping pregnant women in accessing health services? Analysis of the 2014 Ghana demographic and Health survey - Edward Kwabena Ameyaw; Bright Opoku Ahinkorah; Linus Baatiema; Abdul-Aziz Seidu (BMC, 2021)
Abstract Background Increasing the use of healthcare is a significant step in improving health outcomes in both the short and long term. However, the degree of the relationship between utilization of health services and health outcomes is affected by the quality of the services rendered, the timeliness of treatment and follow-up care. In this study, we investigated whether the National Health Insurance Scheme (NHIS) is helping pregnant women in accessing health services in Ghana. Methods Data for the study were obtained from the women's file of the 2014 Ghana Demographic and Health Survey. All women with birth history and aged 15-49  constituted our sample (n = 4271). We employed binary logistic regression analysis in investigating whether the NHIS was helping pregnant women in accessing health service. Statistical significance was set at <0.05. Results Most women had subscribed to the NHIS [67.0%]. Of the subscribed women, 78.2% indicated that the NHIS is helping pregnant women in accessing healthcare. Women who had subscribed to the NHIS were more likely to report that it is helping pregnant women in accessing health service [aOR = 1.70, CI = 1.38-2.10]. We further noted that women who had at least four antenatal visits were more likely to indicate that NHIS is helping pregnant women in accessing health services [aOR = 3.01, CI = 2.20-4.14]. Women with secondary level of education [aOR= 1.42; CI: 1.04-1.92] and those in the richest wealth quintile [aOR = 3.51; CI = 1.94-6.34] had higher odds of indicating that NHIS is helping pregnant women in accessing healthcare. However, women aged 45-49 [aOR = 0.49; CI = 0.26-0.94], women in the Greater Accra [aOR = 0.29; CI = 0.16-0.53], Eastern [aOR = 0.12; CI = 0.07-0.21], Northern [aOR = 0.29; CI = 0.12-0.66] and Upper East [aOR = 0.17; CI = 0.09-0.31] regions had lower odds of reporting that NHIS is helping pregnant women in accessing health services. Conclusion To enhance positive perception towards the use of health services among pregnant women, non-subscribers need to be encouraged to enrol on the NHIS. Together with non-governmental organizations dedicated to maternal and child health issues, the Ghana Health Service's Maternal and Child Health Unit could strengthen efforts to educate pregnant women on the importance of NHIS in maternity care.